Meta-Analysis: Effect of Training and Needle Recapping on Needle Stick Injury in Health Workers - Andriyani, Shofia; Demartoto, Argyo; Murti, Bhisma (Journal of Health Policy and Management, 2024)
Background: Health Personnel are at risk of contracting diseases from blood/body fluids (bloodborne pathogens) in various ways, one of which is through needle stick injuries or what is known as needle stick injury. Recapping of needles and lack of training are factors in unsafe actions that can risk work accidents. This study aims to analyze the effect of training and recapping of needles on the incidence of needle stick injuries in Health personnal using meta analysis. Subjects and Methode: This study is a systematic review and meta-analysis study using the PRISMA diagram. Article searches were carried out based on eligibility criteria using the PICO Model. Population: Health personnal, Intervention: training and not recapping of needles, Comparison: no training and recapping of needles, Outcome: Occurrence of needle stick injury work accidents. The articles used came from Google Scholar, PubMed, Science Direct and ProQuest published from 2013 – 2023. The keywords used in the search were “Training OR Safety Training OR Infection Prevention Training AND Recapping of Needle AND Needle Stick Injury OR Needle Stick Injuries OR Needle Stick and Sharp Injury OR Percutaneous injuries AND Healthcare Workers OR Health Professionals”. The inclusion criteria for this study were full paper articles with cross-sectional studies. The analysis used was multivariate with adjusted Odds Ratio. Eligible articles were analyzed using the Revman 5.3 application. Results: Meta-analysis was carried out on 13 articles originating from the African and Asian continents with a cross-sectional study design. The results of the analysis show that Health personnal who receive training have a risk of experiencing NSI 0.56 times compared to those without training. Although this relationship was not statistically significant (aOR = 0.56; Cl 95% = 0.26 to 1.17; p = 0.120). Recapping of needles has an effect on increasing the incidence of needle stick injuries in health personnel by 2.04 compared to not recapping of needles and this result is statistically significant (aOR=2.04; 95% CI = 1.50 to 2.78; p<0.001) Conclusion: Training and recapping of needles influence the incidence of needle stick injuries in health worker.